Paraproteinemia: blood hyperviscosity and clinical manifestations. - McGrath, M A (1976)
Many of the clinical features of paraproteinemia result from impairment of blood flow through the vascular tree because of blood hyperviscosity. Studies were carried out in 65 patients with serum paraproteins (31 with IgG, 25 with IgM, and 9 with IgA) to examine the relationship between the blood viscosity and the frequency of selected clinical features. The blood and plasma viscosities were measured at low rates of shear. Blood hyperviscosity was present in 91% of the patients and plasma hyperviscosity in 75% of the patients. In each of the three immunoglobulin classes both the blood and plasma viscosities increased logarithmically with the paraprotein concentration being greatest in the case of IgM. In addition, the relationship between the hematocrit and the logarithm of blood viscosity tended to be linear at any given protein concentration. In patients with very high levels of paraprotein the blood viscosity was modified by low hematocrits; the latter was below 30 in 70% of patients in whom the concentration of paraprotein was above 4 g/100 ml. The prevalence of clinical complications involving the retinal circulation, the peripheral vascular system, and the central nervous system increased markedly with increasing blood viscosity, measured at 0.18 S-1. One or more of these regions was affected in greater than 80% of patients with blood viscosity above 60 centipoise and in less than 23% of patients with blood viscosity below 40 centipoise. These observations illustrate the complex relationship between blood viscosity, concentration of paraprotein, immunoglobulin class and hematocrit, and emphasize the importance of measuring the whole blood viscosity at low rates of shear in determining the risk of vascular complications.